Image‐guided core needle biopsy as the first‐line diagnostic approach in lymphoproliferative disorders—A review of the current literature. (20th November 2020) - Seviar, Dale; Yousuff, Mehreen; Chia, Zoe; Ramesar, Keith; Newman, Joel; Howlett, David C.
Abstract: The World Health Organization (WHO) and numerous expert guidelines for lymphoma diagnosis and subclassification advocate the use of histology from surgical nodal excision biopsy (SEB) over core needle biopsy (CNB) due to perceived higher diagnostic yield. CNB is associated with lower morbidity and is more cost‐effective compared to SEB. Furthermore, current practice increasingly demonstrates material obtained from CNB can rapidly diagnose individuals with a clinical suspicion of lymphoma and allow initiation of treatment in the majority of patients. We performed a literature review to assess the suitability of CNB in lymphoma diagnosis given recent advances in radiological and histopathological techniques in obtaining and processing tissue. Additionally, expert international guidelines in lymphoma diagnosis were compared. We found that CNB demonstrated a diagnostic efficacy between 79% and 97% (median 91%) where the diagnostic outcome was conclusive with full lymphoma subclassification. Studies demonstrate that there is a high diagnostic reproducibility amongst haematopathologists (87%‐93%) in lymphoma diagnoses with full subtyping from material obtained via CNB. Furthermore, CNB is a safe, rapid and reliable method of obtaining tissue from lymph nodes for histopathological analysis. These procedures are minimally invasive, well‐tolerated and should be considered the first‐line diagnostic approach in clinical practice in patients with suspected lymphoproliferative disorders.